A Predicativist Semantics of Modals based on Modal Objects - Moltmann, Friederike (Proceedings of the Amsterdam Colloquium, 2015)
I will outline a novel ‘predicativist’ semantics of modals in natural language, by focusing not on possible worlds and quantifiers ranging over them, but on what I will call modal objects and their satisfaction conditions.